Menginvestigasi Keefektifan Perubahan Di Perguruan Tinggi Menggunakan Analisis 7s Mckinsey - Setya Indah Isnawati; Suharnomo Suharnomo; Ahyar Yuniawan (Universitas Ngudi Waluyo, 2020)
This study aims to determine the effectiveness of the organization to the changes using McKinsey 7S analysis. The method used is qualitative research with case study approach. Results of the study revealed that the factor changes in the UNW is commitment and loyalty of employees, roles and skills of human resources, development of potential human resources, organizational development and technological progress. Based on McKinsey 7S, also found changes that occur in each of its component S, where each component still requires a change in achieving an effective organization. Changes in UNW also includes the metaphor of the organization as a machine, in which these changes have been effective.